2020
DOI: 10.1158/1078-0432.ccr-20-2066
|View full text |Cite
|
Sign up to set email alerts
|

Electronic DNA Analysis of CSF Cell-free Tumor DNA to Quantify Multi-gene Molecular Response in Pediatric High-grade Glioma

Abstract: Purpose: Pediatric high-grade glioma (pHGG) diagnosis portends poor prognosis and therapeutic monitoring remains difficult. Tumors release cell-free tumor DNA (cf-tDNA) into cerebrospinal fluid (CSF), allowing for potential detection of tumor-associated mutations by CSF sampling. We hypothesized that direct, electronic analysis of cf-tDNA with a handheld platform (Oxford Nanopore MinION) could quantify patient-specific CSF cf-tDNA variant allele fraction (VAF) with improved speed and limit of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Nanopore sequencing is a relatively new technology ( 57 ) that has been used for liquid biopsies ( 58 , 59 ). Nanopore sequencers work by feeding DNA strands through small pores embedded in a membrane.…”
Section: Cf-tdna Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanopore sequencing is a relatively new technology ( 57 ) that has been used for liquid biopsies ( 58 , 59 ). Nanopore sequencers work by feeding DNA strands through small pores embedded in a membrane.…”
Section: Cf-tdna Detection Methodsmentioning
confidence: 99%
“…Nanopore devices are low-cost, can sequence any length DNA strand, have a small form factor, and offer a rapid time to result making them ideal devices for liquid biopsy. However, the device’s error rate has traditionally prevented it from being applied to liquid samples where allele frequencies are less than ~2% ( 58 ). Our group previously analyzed CSF samples from 12 pediatric high grade glioma patients and found that nanopore had a 85% sensitivity and 100% specificity in CSF samples ( 58 ), which compared favorably to Illumina-based targeted sequencing.…”
Section: Cf-tdna Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR primer sets were drawn from multiple sources and selected or designed to flank the HIST1H3B K27M hotspot mutation. The 187 bp primer set was taken from prior work 39 . The 260 bp primer set was designed using Primer3 v4.1.0 and tailed at the 5' ends with ONT handshake sequences to enable potential interoperability with ONT's four-primer library preparation protocol.…”
Section: Methodsmentioning
confidence: 99%